A bibliometric analysis of research for climate impact on agriculture - Wu, You; Meng, Shuhan; Liu, Chaoshun; Gao, Wei; Liang, Xin-Zhong (Frontiers in Sustainable Food Systems, 2023)
Climate anomalies and changes have complex and critical impacts on agriculture. Given global warming, the scientific community has dramatically increased research on these impacts. During 1996–2022, over 3,000 peer-reviewed papers in the Web of Science Core Collection database have investigated the fields. This study conducted a bibliometric analysis of these papers for systematic mapping and inductive understanding to comprehensively review the research’s status, focus, network, and funding. After almost 30 years, the research is now centered in quantifying climate impacts on crop yields and agriculture productivity while seeking effective adaptation solutions. The hot keywords recently emerged include poverty, food security, water resource, climate service, climate-smart agriculture, sustainability, and policy. They suggest increasing concerns on global food and water shortage and pressing needs for action to adapt to climate change and sustain agricultural productivity. Given the uncertainty of climate change and the complexity of agriculture systems, most current studies are interdisciplinary research combining various agricultural fields with climate, environmental, and socioeconomic sciences. The United States, as the world’s leading food commodity producer, has the most diverse funding agencies and provides the largest number of awards to support the research. Future priority research should take the coupled earth system approach with the food-energy-water nexus principles to provide effective, actionable decision supports at local-regional scales to sustain national agricultural productivity and quantify climate-smart agricultural practices to mitigate global warming.